Microbial Diversity in the Peri-Implant Region of Patients with History of Periodontal Disease and Clinical Parameters (Research, Society and Development, 2022)
Although implant rehabilitations are successful, a small portion of patients may present peri-implant mucositis and peri-implantitis due to the bacteria biofilm formation. The purpose of the present study was to evaluate the presence of Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Fusobacterium nucleatum (Fn) and Scardovia wiggsiae (Sw) in Peri-implant gingival Fluid (PGF) of patients who received implants 12 months ago and associated with periodontitis (PD) history and clinical data. Samples were collected from 44 volunteers and analyzed by PCR with specific primers. The results showed that Pg were detected in 34%, Fn and Pi, 81.8%, and Sw 75% of the volunteers. Pg was frequently detected in patients who had a history of PD (p0.05, q